Accuracy and Reliability of Commercial Wrist-Worn Pulse Oximeter During Normobaric Hypoxia Exposure Under Resting Conditions. Issue 3 (3rd July 2021) - Lauterbach, Claire J.; Romano, Phebe A.; Greisler, Luke A.; Brindle, Richard A.; Ford, Kevin R.; Kuennen, Matthew R.
ABSTRACT: Purpose : The present study analyzed peripheral blood oxygen saturation (Sp O2 ) and heart rate (HR) measurements taken on the Garmin fēnix® 5X Plus watch, comparing them to measurements taken on a standard medical-grade pulse oximeter during normobaric hypoxia exposure under resting conditions. Methods : Thirteen women (mean ± SD: Age 20 ± 1 years, height 165 ± 5 cm, mass, 67 ± 9 kg) and ten men (mean ± SD: Age 21 ± 3 years, height 177 ± 6 cm, mass 78 ± 11 kg) sat inside a customized environmental chamber while the fraction of inspired oxygen (FI O2 ) was adjusted to simulate altitudes of 12, 000; 10, 000; 8, 000; 6, 000; and 900 ft. The novel commercial device (Garmin fēnix®) and a medical-grade pulse oximeter (Nonin® 7500) were used to measure Sp O2 and HR in triplicate at each simulated altitude. Bland–Altman analyses were used to assess differences between methods. Results : Bland–Altman analysis indicated 3.3% bias for Sp O2 measurements taken on the Garmin fēnix® at 12, 000 ft of simulated altitude (limits of agreement: −1.9–8.6%). Mean differences in Sp O2 measurements were smaller at the remaining simulated altitudes, where bias measurements ranged from 0.7% to 0.8%. The Garmin fēnix® also underestimated heart rate, but those discrepancies were minimal (bias measurements at all simulated altitude exposures were < 1.0 bpm). Conclusions : With the exception of readings taken at 12, 000 ft of simulated altitude, the Garmin fēnix® exhibits minimal overestimation of Sp O2 and minimal underestimation of HR during simulated altitude exposure. These data suggest the Garmin fēnix® watch may be a viable method to monitor Sp O2 and HR under most ambient environmental conditions.